SEKULARISME DI BARAT - Wantika, Ayu; Fitriani, Fitriani (UIN Sumatera Utara Medan, 2024)
Secularism, which comes from the Latin word 'saeculum' meaning age, is an ideology that separates religion from government affairs and public life. In the West, secularism emerged in response to the domination of the church and the suppression of freedom of thought during the Middle Ages. This ideology is growing rapidly along with the advancement of science and technology, which is often contrary to religious dogma. Secularism in the West has various models, such as the French model that emphasizes the total separation between religion and the state, as well as the AngloAmerican model that emphasizes more on the neutrality of the state in religious affairs. This article examines the history, causal factors, and impacts of secularism in the West, as well as how this ideology affects the social, political, and cultural life of Western societies.Keywords: Secularism, West, Separation of religion and state.